Dietary patterns and cardiometabolic health: Clinical evidence and mechanism. Issue 1 (5th February 2023) - Wang, Wenting; Liu, Yanfei; Li, Yiwen; Luo, Binyu; Lin, Zhixiu; Chen, Keji; Liu, Yue
Abstract: For centuries, the search for nutritional interventions to underpin cardiovascular treatment and prevention guidelines has contributed to the rapid development of the field of dietary patterns and cardiometabolic disease (CMD). Numerous studies have demonstrated that healthy dietary patterns with emphasis on food‐based recommendations are the gold standard for extending lifespan and reducing the risks of CMD and mortality. Healthy dietary patterns include various permutations of energy restriction, macronutrients, and food intake patterns such as calorie restriction, intermittent fasting, Mediterranean diet, plant‐based diets, etc. Early implementation of healthy dietary patterns in patients with CMD is encouraged, but an understanding of the mechanisms by which these patterns trigger cardiometabolic benefits remains incomplete. Hence, this review examined several dietary patterns that may improve cardiometabolic health, including restrictive dietary patterns, regional dietary patterns, and diets based on controlled macronutrients and food groups, summarizing cutting‐edge evidence and potential mechanisms for CMD prevention and treatment. Particularly, considering individual differences in responses to dietary composition and nutritional changes in organ tissue diversity, we highlighted the critical role of individual gut microbiota in the crosstalk between diet and CMD and recommend a more precise and dynamic nutritional strategy for CMD by developing dietary patterns based on individual gut microbiota profiles. Abstract : The research process for analyzing nutrition and cardiometabolic health is shown in a bottom–up manner. Phase 1: identification of essential nutrients and healthy foods, such as vegetables and fruits, whole grains, and plant‐based oils (tier 4). Phase 2: establishment and development of different types of dietary patterns, such as vegetarian diets, Mediterranean diets, ketogenic diets, calorie restriction, and intermittent fasting (tier 3). Phase 3: exploration of the molecular mechanisms of dietary interventions, including nutrient response pathways, immune regulation, the role of gut microbiota and metabolites, and circadian rhythms (tier 2). Phase 4: providing personalized dietary strategies to cardiometabolic disease patients based on diet–genetic interactions (tier 1).